Ginsenoside RH1 Improves Neurological Function By Inhibiting Oxidative Stress and Promoting the Expression of Neurotrophic Factors in Cerebral Ischemia-Reperfusion Rats - tian, Wang; Guirong, Zhang; Sensen, Wang; Mingyue, Li; Qinpin, Zheng; Xue, Jia (Asian Journal of Pharmaceutical Research and Development, 2024)
Ginseng, a valued herb in China, showed efficacies for treatment or prevention of a series of conditions in patients. Ginsenoside Rh1 is the major active component of ginseng. The aim of this study was to investigate the neuroprotective effects of ginsenoside Rh1 on injury of cerebral ischemia-reperfusion in rats. Middle cerebral artery occlusion and reperfusion were performed in male Sprague-Dawley rats. The ischemic stroke rats were treated with ginsenoside Rh1 at dose of 5 mg/kg and 10 mg/kg by gavage. After 7-day treatment, neurological functions of animals were evaluated by adhesive removal tape and beam walking tests. Neuron injury was assessed by immunohistochemical staining. The levels of MDA, BDNF, NGF and activities of SOD, CAT in the ischemic hemisphere were assayed. Treatment with ginsenoside Rh1 for 7 days could significantly improve the neurological functions (P < 0.05)and increase the number of NeuN-positive cells in rats with cerebral ischemia(P < 0.01).Ginsenoside Rh1 decreased significantly MDA level(P < 0.01) and enhanced activitiesof SOD, CAT (P < 0.05 or P < 0.01).Further measurement showed that ginsenoside Rh1 also increased the levels of BDNF, NGF of the ischemic hemisphere(P<0.05 or P<0.01).The present findings demonstrated that ginsenoside Rh1 improved neurological function by inhibiting oxidative stress and promoting the expression of neurotrophic factors after cerebral ischemia-reperfusion.